(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The archaeological site of Dortash, which dates back to the 1st millennium BC, has been protected by the state due to its antiquity. In a unique location at the foot of the Bandikhan mountain, which connects Kadim Chaganiyon with Maverunnahr, there was a Friday market where people would gather.